Shape memory alloy based smart link for aircraft wing structure:FE modelling and experiments - Vasanthanathan, A.; Nagaraj, P.; Raja, K. Karthick; Arjun, R. Kumar; Rajakalai, M. (Journal of Structural Engineering, 2024)
This article emphasizes on the development of Shape Memory Alloy (SMA) based smart link for the flight control system. SMA are the candidate material for the actuation of smart structures due to its Shape Memory Effect (SME). In this paper, Nitinol® is used as an SMA which is of 55% Titanium and 45% Nickel. Nitinol® in spring form, proposed in the present paper actuates the aileron which is a primary flight control system through a smart link system. The aileron facilitates the rolling motion of an aircraft. Due to symmetry, this paper addresses the actuation of aileron in one wing. Both experiments and finite element modelling are carried out. The finite element modelling of a cylindrical portion of SMA was performed so as to numerically exhibit the SME. The finite element simulation of the aileron actuation was performed by incorporating the effect of SMA spring. The finite element analysis reveals that as the temperature exceeds the phase transformation temperature (Tp), the material regain its original shape. The finite element analysis of SME was computed using ANSYS® Mechanical APDL 17.2 environment while the aileron actuation was simulated in ANSYS® 16.0 Rigid Dynamics environment. The SMA spring are actuated by heating to its phase transformation temperature. Analytical calculations are also presented for the detection of current value to be supplied into the SMA spring. Experiments are conducted in a Glass Fabric Reinforced Plastic (GFRP) wing model and the actuation of smart link has been investigated.